Dilution effect of TEMPO-oxidized cellulose nanofibers on reproduction of Daphnia magna - Hiroyuki Mano; Rie Tai; Akihiro Moriyama; Yoko Iizumi; Tomohiko Matsuzawa; Toshiya Okazaki; Isamu Ogura (Ecotoxicology and Environmental Safety)
The expanding use of 2,2,6,6-tetramethylpiperidine-1-oxyl radical-oxidized cellulose nanofibers (TEMPO-CNFs) raises concerns about their environmental release and potential ecological impacts. Evaluating their environmental effects is critical for ensuring their sustainable use. In this study, we aimed to assess the ecotoxicity of TEMPO-CNFs on Daphnia magna reproduction and explore mechanisms underlying observed effects. Reproductive toxicity was evaluated according to the Organisation for Economic Co-operation and Development test guideline, determining the no observed effect concentration (NOEC) and 10 % effect concentration (EC10). Mechanistic insights were investigated through water chemistry analyses, a feeding inhibition test, a gut evacuation experiment, and 10-day life table experiments. The NOEC and EC10 for TEMPO-CNFs were 12.5 mg/L and 3.4 mg/L, respectively. Results supported the dilution-effect hypothesis, indicating reduced availability of essential food, such as Chlorella, as a driver of toxicity. Gut evacuation experiments indicated that TEMPO-CNFs in D. magna individuals were excreted within 24 h when they were transferred to a CNF-free environment. The results suggest that TEMPO-CNFs are unlikely to impact D. magna reproduction unless exposure is continuous and at high concentrations. These findings support the environmentally sustainable application of TEMPO-CNFs with controlled exposure.